Pengaruh lama mengunyah terhadap kadar glukosa postprandial dewasa obesitas - Wulansari, Arin; Luthfinnisa, Fryta Ameilia; Uyun, Fuadah; Retnoningrum, Dwi; Rahmi, Fifin Luthfia; Wildan, Arief (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: Obesity cause various physiological changes in the body, one of which is insulin resistance causes high blood glucose levels. Chewing is a stimulus of cephalic phase responses and sensory stimulation that can increase hormones releasing such as insulin, ghrelin, cholecystokinin (CCK) and glucagon like peptide-1 (GLP-1). Chewing plays important role in determining postprandial plasma glucose concentration.Objective: Investigate the effect of chewing on postprandial blood glucose in obese adults.Method: This was true experimental research. Research subjects were treated in the form of chewing 22 times and 40 times each mouthful. Blood glucose levels were measured using glucometer on fasting blood glucose and postprandial blood glucose 15 minutes, 30 minutes, 60 minutes, and 120 minutes. Statistical test using Independent t-test.Results: The mean postprandial glucose levels in the 22 chews group at 15 minutes, 30 minutes, 60 minutes, and 120 minutes were 112.11 ± 14.3328, 126.11 ± 15.667, 116.94 ± 15.539, and 89.67 ± 11.668 . While the mean postprandial blood glucose levels in the 40 chews group at 15 minutes, 30 minutes, 60 minutes, and 120 minutes were 122.22 ± 14.381, 129.61 ± 15.112, 109.50 ± 14.995, and 85.83 ± 13.963. There were statistically significant differences between chewing groups 22 times and chewing 40 times on fasting blood glucose and 15 minutes postprandial blood glucose (p = 0.041 and p = 0.042), while on 30 minutes postprandial glucose testing, 60 minutes , and 120 minutes there was no significant difference (p> 0.05).Conclusion: There was significant differences in 15 minutes postprandial blood glucose level between group 22 times chewing and 40 times chewing each mouthful.